A poly-herbal blend (Herbagut®) on adults presenting with gastrointestinal complaints: a randomised, double-blind, placebo-controlled study - Adrian L. Lopresti; Hemant Gupta; Stephen J. Smith (BMC, 2018)
Abstract Background To evaluate the efficacy and tolerability of a poly-herbal formulation, Herbagut, for the treatment of gastrointestinal symptoms and its effect on quality of life parameters in patients presenting with self-reported, unsatisfactory bowel habits. Methods This was a randomised, double-blind, placebo-controlled trial. Fifty adults with self-reported unsatisfactory bowel habits, primarily characterised by chronic constipation were randomly allocated to take Herbagut or a matching placebo for 28 days. Efficacy of gastrointestinal changes was measured by the completion of a patient daily diary evaluating changes in stool type (Bristol Stool Form Scale), ease of bowel movements, and feeling of complete evacuation; and the Gastrointestinal Symptom Rating Scale (GSRS). Changes in quality of life were also examined using the World Health Organization Quality of Life - abbreviated version (WHOQOL-BREF), and the Patient Assessment of Constipation-Quality of Life (PAC-QOL). Results All participants completed the 28-day trial with no adverse events reported. Compared to the placebo, weekly bowel movements increased over time (p < .001), as did self-reported, normal bowel motions (76% vs 4%; p < .001). Self-reported incomplete evacuation was also lower in the Herbagut group compared to placebo (24% vs 76%; p = <.001). GSRS domain ratings for abdominal pain, constipation, diarrhoea, indigestion, and reflux also decreased significantly in people taking Herbagut compared to placebo (p < .001, for all domains). Moreover, quality of life significantly improved in the Herbagut group compared to placebo as indicated by significantly greater improvement in WHOQOL-BREF domain ratings for overall quality of life, social relations, environmental health, psychological health, and physical health (p < .001, for all domains); and PAC-QOL domain ratings for physical discomfort, psychosocial discomfort, worries and concerns, and life satisfaction (p < .001, for all domains). The changes were considered clinically meaningful as evidenced by their large effect sizes. Conclusion Herbagut ingestion over a 28-day period resulted in improvements in several gastrointestinal symptoms and overall quality of life. Further investigation utilising larger sample sizes and diverse clinical and cultural populations are needed. Trial registration Clinical Trials Registry- India /2016/11/007479. Registered 24 April 2015 (retrospectively registered).